(untitled) (Innovate Conferences, 2025)
One of the urgent problems of today is the purification of drinking water and the supply of high-quality drinking water to the population. It is established in Article 24 of Chapter 6 of the Decree of the Republic of Uzbekistan No. ORQ-784 dated 22.07.2022 on drinking water supply and wastewater disposal. According to the resolution, it is envisaged to carry out the preparation and supply of drinking water and the technological stages of drinking water preparation in water facilities, taking into account the quality of water in the water body, the capacity of the facility and its geographical location. In finding optimal solutions for the technological processes of drinking water preparation in water facilities, proposals and considerations were made on the optimal selection of materials used as fillers in rapid filters and the provision of high-quality and required drinking water to the population